MODALIZATION IN HEALTH PUBLIC SERVICE ADVERTISEMENT: A SYSTEMIC FUNCTIONAL GRAMMAR STUDY - Ponia Mega Septiana; Imam Muhtadi; Wiwi Sari (Faculty of Letters Universitas Balikpapan, 2024)
Using a systemic functional grammar approach, this research looks for modalization in health public service announcements. A descriptive qualitative method is used in this study. A component of modality that is elaborated in interpersonal Meta function, known as